Capturing the pupil voice of secondary gifted and talented students who had attended an enrichment programme in their infant school. (January 2014) - Houghton, Chris
The study was conducted during the Easter holidays of 2010 at Rawmarsh City Learning Centre with 16 students from school years 8 to 11 who had participated, during their infant years, in a gifted and talented Key Stage One Enrichment Cluster. The students represented a wide range of backgrounds, and five were identified as being on the autistic spectrum. The Enrichment Cluster was known as original ways of learning through enrichment technology and socialisation (OWLETS). OWLETS aimed to address the lack of provision for exceptionally able young children, while supporting them in overcoming any weaknesses in relation to socialisation or engagement. The cluster design was inspired by Renzulli's Schoolwide Enrichment Model. The study investigated the students' perspective of key features of their experiences at OWLETS and throughout their subsequent education, examining their views on learning and teaching, and was facilitated by the production of a video with student voices spoken by avatars. Findings showed that those with additional special needs preferred primary school and described struggles in secondary; the other 11 students were more positive about secondary education than primary. All the students viewed opportunities for personalised learning and effective teacher–student relationships as key, and they suggested that children who demonstrate exceptional ability benefit from opportunities to socialise and work collaboratively with similarly gifted peers throughout all stages of education. The study indicated that Renzulli's model, in this simple format, has the potential to enrich a whole-school approach, meeting the needs of all children including the exceptionally able.